An epidemiological analysis of the burden of chronic thromboembolic pulmonary hypertension in the USA, Europe and Japan - Gall, Henning; Hoeper, Marius M.; Richter, Manuel J.; Cacheris, William; Hinzmann, Barbara; Mayer, Eckhard (European respiratory review, 2017)
Epidemiological data for chronic thromboembolic pulmonary hypertension (CTEPH) are limited and there are conflicting reports regarding its pathogenesis. A literature review was conducted to identify CTEPH epidemiological data up to June 2014. Data were analysed to provide estimates of the incidence of CTEPH in the USA, Europe and Japan. An epidemiological projection model derived country-specific estimates of future incidence and diagnosis rates of CTEPH. Overall, 25 publications and 14 databases provided quantitative epidemiological data. In the USA and Europe, the crude annual incidence of diagnosed pulmonary embolism and crude annual full ( i.e. diagnosed and undiagnosed) incidence of CTEPH were 66–104 and 3–5 cases per 100 000 population, respectively, while in Japan these rates were lower at 6.7 and 1.9 per 100 000 population, respectively. In 2013, 7–29% of CTEPH cases in Europe and the USA were diagnosed, and the majority of patients were in New York Heart Association functional class III/IV at diagnosis. The projection model indicated that incidence of CTEPH will continue to increase over the next decade. These data suggest that CTEPH is underdiagnosed and undertreated, and there is an urgent need to increase awareness of CTEPH. High-quality epidemiological studies are required to increase understanding of CTEPH.